Structuring a knowledge-based maritime cluster: contributions of network analysis in a tourism region - Pinto, H. (2012)
The notion of maritime cluster encompasses a diversity of activities from fi sheries, aquaculture, transports to coastal tourism or even science-based activities. This article debates the possibilities to consolidate the maritime cluster as one of the driving forces of the Algarve, a Portuguese region internationally recognized by tourism. This cluster did not emerge spontaneously and several policy initiatives to promote its formalization were being developed. The regional actors are not sure about the organizations that can be mediators in the cluster. Using social network analysis the maritime cluster is mapped, identifying central actors and possible structural holes. Policy implications are underlined.